PH dependent photocatalytic hydrogen evolution by self-assembled perylene bisimides. Issue 16 (6th April 2017) - Nolan, Michael C.; Walsh, James J.; Mears, Laura L. E.; Draper, Emily R.; Wallace, Matthew; Barrow, Michael; Dietrich, Bart; King, Stephen M.; Cowan, Alexander J.; Adams, Dave J.
Abstract : We show the importance of the self-assembly of a perylene bisimide on its photocatalytic activity. Abstract : There is growing interest in the design of supramolecular structures that are photocatalytically active. Perylene bisimides can be self-assembled to produce structures for photocatalytic hydrogen evolution. Herein we explore the role of pH in controlling self-assembly and photocatalysis. It is shown that self-assembly, which occurs as the pH of the system is decreased, is required for hydrogen evolution to occur.